Exploiting Genic Male Sterility in Rice: From Molecular Dissection to Breeding Applications - Abbas, Adil; Yu, Ping; Sun, Lianping; Yang, Zhengfu; Chen, Daibo; Cheng, Shihua; Cao, Liyong (Frontiers in Plant Science, 2021)
Rice (Oryza sativa L.) occupies a very salient and indispensable status among cereal crops as its vast production is used to feed nearly half of the world’s population. Male sterile plants are the fundamental breeding materials needed for specific propagation in order to meet the elevated current food demands. The development of the rice varieties with desired traits has become the ultimate need of the time. Genic male sterility is a predominant system that is vastly deployed and exploited for crop improvement. Hence, the identification of new genetic elements and the cognizance of the underlying regulatory networks affecting male sterility in rice is crucial to harness heterosis and ensure global food security. Over the years, a variety of genomics studies have uncovered numerous mechanisms regulating male sterility in rice, which provided a deeper and wider understanding on the complex molecular basis of anther and pollen development. The recent advances in genomics and the emergence of multiple biotechnological methods have revolutionized the field of rice breeding. In this review, we have briefly documented the recent evolution, exploration and exploitation of genic male sterility to the improvement of rice crop production. Furthermore, this review describes future perspectives with focus on state of art developments in the engineering of male sterility to overcome issues associated with male sterility-mediated rice breeding to address the current challenges. Finally, we provide our perspectives on diversified studies regarding the identification and characterization of genic male sterility genes, the development of new biotechnology-based male sterility systems and their integrated applications for hybrid rice breeding.